Analisa Association Rule Terhadap Perilaku Konsumtif Mahasiswa pada Promo Tanggal Kembar Shopee - Yulya Muharmi; Nurul Azwanti; Sri Tria Siska; Dhella Amelia (JSAI (Journal Scientific and Applied Informatics), 2024)
Student consumer behavior, especially during big promotions such as twin dates, often raises concerns regarding the balance between needs and wants, as well as the impact on personal finances. This research aims to analyze student purchasing patterns using the Association Rule method and understand how the twin date promo at Shopee influences the consumer behavior of students in the STT Payakumbuh department majoring in D3 Computer Engineering. It was found that products that were often purchased simultaneously during twin date promotions included products with high discounts or attractive cashback. Using the Apriori algorithm, this research identifies relationships between products that are frequently purchased together, and reveals a significant influence between large discounts and increased purchasing frequency. The analysis results show support of 30% and confidence of 80%, with a tendency to buy Hijab with Skincare and HP Accessories with Fashion. It is hoped that this research can provide insight for marketplace managers, especially Shopee, in designing more effective promotions and helping students make wiser consumption decisions. Even though there are limitations in product specifications, the results of this research provide an important contribution in understanding student consumer behavior in the online shopping era and the importance of targeted marketing strategies.